The Essence of Muallaf as a Zakat Recipient According to the Interpretation of Surah At-Tawbah Verse 60 - Nainunis, Nainunis; Abubakar, Al Yasa'; Sabil, Jabbar; Iqbal, Muhammad; Saputra, Dian (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2025)
Muallaf (new converts to Islam) are one of the eight categories (asnaf) entitled to receive zakat, as mentioned in Surah At-Tawbah verse 60. However, the essence and criteria of muallaf are not clearly defined, raising questions about who truly qualifies under this category. This study aims to examine the concept of muallaf from the perspective of maqāṣid al-sharī‘ah by analyzing relevant textual evidence, including hadiths and Qur’anic exegesis. The research employs a library research method to explore and examine data from literary sources in depth. The process includes collecting, reviewing, recording, and processing relevant references. More than mere reading and documentation, library research demands analytical skills to produce systematic and meaningful findings. This study adopts a qualitative normative approach. Specifically, it falls under the category of normative Islamic legal research with a philosophical orientation, as it seeks to uncover and understand the core values and fundamental principles within Islamic legal norms that guide legal reasoning. The findings of this study, based on the interpretation of Surah At-Tawbah verse 60, categorize muallaf into two groups: Muslim muallaf and non-Muslim muallaf. The former includes: individuals newly converted to Islam whose faith is still fragile; respected Muslims who lead their communities; Muslims willing to strive and engage in jihad against non-believers; and Muslims needed to collect zakat from those unwilling to give. The latter group consists of: individuals expected to convert to Islam, and individuals whose harm is feared